2021
DOI: 10.1002/slct.202100235
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of CO2 on Flame Annealed Cu

Abstract: Surface modification of metallic Cu by conventional oxidation and an alternative method of oxidation using flame annealing and its influence on electrochemical reduction (ECR) of CO 2 are reported in this study. The ECR of CO 2 in aqueous KCl electrolyte yielded methane, ethane, ethylene, and hydrogen as the major products. The faradaic efficiency of ethane obtained at À 1.2 V vs NHE for flame-annealed Cu (34 %) was comparable to the conventionally oxidised Cu (40 %), while bare Cu yielded methane (10 %). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have been carried out on Cu and its derivatives, including oxides, , alloys, different Cu substrates, , Cu/carbon-based materials, , and Cu used with molecular catalysts, , with the aim of enhancing CO 2 reduction activity and adjusting product selectivity. Sujet et al prepared a Cu nanofoam structure on Cu foil and observed CO 2 reduction at more positive potential compared to smooth Cu foil, with a maximum faradaic efficiency (FE) of 37% for formate achieved at −1.5 V vs Ag/AgCl.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been carried out on Cu and its derivatives, including oxides, , alloys, different Cu substrates, , Cu/carbon-based materials, , and Cu used with molecular catalysts, , with the aim of enhancing CO 2 reduction activity and adjusting product selectivity. Sujet et al prepared a Cu nanofoam structure on Cu foil and observed CO 2 reduction at more positive potential compared to smooth Cu foil, with a maximum faradaic efficiency (FE) of 37% for formate achieved at −1.5 V vs Ag/AgCl.…”
Section: Introductionmentioning
confidence: 99%